(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The study aims to substantiate the impact of traditional Korean medicine methods on patients’ quality-of-life parameters using medical and sociological research data. The study involved 152 patients diagnosed with lumbosacral dorsopathy: 54 (35.5%) men and 98 (64.5%) women, aged 21-71 years, with an average age of 52±8.4 years. Patients were randomized into four groups based on the applied pain management techniques: Group I (36 patients, 23.7%) received standard complex medication therapy (MT), Group II (32 patients, 21.1%) received MT combined with traditional Korean therapy (TKT) for chronic pain, Group III (45 patients, 29.6%) received standard drug therapy combined with transcranial magnetic stimulation (TMS), Group IV (39 patients, 25.7%) received TMT combined with TMS. The Oswestry Disability Index (ODI) questionnaire was used to assess quality of life (QoL) before and after therapy. Comparative analysis of ODI parameters before therapy showed high disability index scores across all four groups, exceeding 50%. After treatment: Group IV (TKT + TMS) showed an ODI of 0%, a statistically significant improvement compared to: Group I (MT only): ODI = 14%, Group II (MT + TKT): ODI = 6%, Group III (MT + TMS): ODI = 10%. Patients with chronic pain associated with lumbosacral dorsopathy exhibit low QoL indicators. The study highlights that combined treatment methods, particularly traditional Korean therapy, provide significant long-term benefits over standard drug therapy alone. This supports the increasing integration of traditional Korean medicine for managing chronic pain.